2022
DOI: 10.3389/fpls.2021.764625
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Metabolome and Transcriptome Studies Reveals Flavonoids, Abscisic Acid, and Nitric Oxide Comodulating the Freezing Tolerance in Liriope spicata

Abstract: Liriope spicata is an evergreen perennial ornamental groundcover with a strong freezing tolerance. However, the molecular mechanism underlying the freezing tolerance in L. spicata remains unclear. In this study, a comprehensive investigation of L. spicata freezing tolerance was conducted at the levels of physiology and biochemistry, metabolite, and transcript during the stress treatment. There were 581 unique differentially expressed metabolites (DEMs) and 10,444 unique differentially expressed genes (DEGs) be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“… Qin et al (2022) studied the response mechanism of two kinds of Lycium barbarum under salt stress through transcriptomics and metabolomics and revealed the intrinsic reason for the high salt tolerance of L. barbarum . By integrating metabolomic and transcriptomic studies, Peng et al (2021) revealed that flavonoids, abscisic acid, and nitric oxide jointly regulate the frost resistance of Liriope spicata and identified the involvement of the flavonoid pathway, abscisic acid biosynthesis, and the genes and metabolites of NO oxidative synthesis to construct a comprehensive network of frost resistance of L. spicata .…”
Section: Introductionmentioning
confidence: 99%
“… Qin et al (2022) studied the response mechanism of two kinds of Lycium barbarum under salt stress through transcriptomics and metabolomics and revealed the intrinsic reason for the high salt tolerance of L. barbarum . By integrating metabolomic and transcriptomic studies, Peng et al (2021) revealed that flavonoids, abscisic acid, and nitric oxide jointly regulate the frost resistance of Liriope spicata and identified the involvement of the flavonoid pathway, abscisic acid biosynthesis, and the genes and metabolites of NO oxidative synthesis to construct a comprehensive network of frost resistance of L. spicata .…”
Section: Introductionmentioning
confidence: 99%
“…Secondary metabolites participate in plant growth, development, and adaptation, and may in addition play important roles in plant defense against pathogens and abiotic stress ( Bednarek and Osbourn, 2009 ; Peng et al., 2021 ). Triterpenoid saponins are known as a vital class of secondary metabolites with important medicinal value ( Ge et al., 2016 ; Yan et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…at low temperatures (24). Peng et al studied L. Spicata's avonoid biosynthesis, carbohydrate metabolism, amino acid metabolism, lipid metabolism, and signaling pathways are signi cantly enriched in response to cryostress (25). Lv et al found that the differential expression of P-coumarinamide, D-proline, betaine, and chlorogenic acid metabolites in wheat under low temperature conditions, and seven upregulated metabolites and eight upregulated key enzymes were also closely involved in the biosynthetic pathway of sucrose and amino acids (26).…”
Section: Introductionmentioning
confidence: 99%